Éduquer dans un monde pluraliste : le minimalisme moral au secours de l’école républicaine ? - Vincent Lorius (Recherches en Éducation)
The moral minimalism is characterized primarily by its reference to a no harm principle (OGIEN, 2007). Is this moral option which seems inherently incompatible with the education, still mobilized in school educational practices? If it is, is it a problem in terms of republican school’s objectives and the role that educators should have? Enlightened by a current survey, we can propose some arguments in favor of a positive answer to the first question and negative to the second one. By pressing us on interviews with some professionals of school education, we actually try to show that they mobilize, in their practises, a variety of moral compass, of which some are from minimalism. Then, We can argue that, to educate in a pluralistic world, education stakeholders need to be themselves pluralistic, individually and practically. So, the question that arises is not to know whether minimalism can be a barrier in education, but is to know how could we caracterize it specific interest to contribute to a republican education’s project.